European integration studies, European Monetary Union, and resilience of austerity in Europe: Post-mortem on a crisis foretold. (April 2015) - Cafruny, Alan W
Europe's Economic and Monetary Union was presented in terms of an idealized, teleological narrative of 'ever closer union' that obscured substantive conflicts within and among the member states of the eurozone as well as the EU as a whole. Despite its limitations the narrative persisted, because it was instrumentalized by powerful social forces and states and reproduced by the mainstream European studies academic cohort, which was strongly influenced by the European Commission. At the present time economic stagnation is giving rise to demands from Keynesian and heterodox quarters for an alternative to neoliberal austerity. However, the resilience of austerity should be understood not primarily as a result of a dominant, if flawed, intellectual discourse, but rather as an expression of Europe's distinctive power relations and the imperatives of German export mercantilism.